The Use of Web-Based Vocabulary Games to Improve Junior High School Students’ Vocabulary Mastery in Reading - Putri, Ananda Sadyva Aulia; Akhiriyah, Suvi (JET (Journal of English Teaching), 2024)
Web-based game can be an alternative learning media for students to improve their vocabulary mastery in reading. Nevertheless, few studies look at how web-based games can be used as a teaching tool to help junior high school students improve their vocabulary, especially in context of reading. The main objective of this research is to know the differences between the improvement of vocabulary mastery of 7 grade students at a junior high school in Indonesia who use the web-based vocabulary game "WordWall" compared to those who do not. This research was carried out using a quasi-experimental design by using Pre-test and Post-test as the instruments. Furthermore, as research participants, there were two classes from one of the junior high schools in Surabaya: 7E which was the experimental group (N=31), and 7F students became the control group (N=31). The findings of this research showed that the significance value <0.05 was achieved (0.00), and it indicates that there is a significant difference in the results of learning vocabulary between the experimental group and the control group. It can be concluded that using web-basaed game has a significant impact on students’ improvement in vocabulary mastery in reading than those who do not.